Phase Changes of Electromagnetic Oceanic Tidal Signals - Saynisch‐Wagner, J.; Petereit, J.; Irrgang, C.; Thomas, M.; 1 Earth System Modelling, Helmholtz Centre Potsdam GFZ German Research Centre Potsdam Germany (Journal of Geophysical Research: Oceans, 2020)
Over the last years, the number of studies that investigate or utilize the electromagnetic (EM) signals generated by ocean tides is steadily growing. However, the majority of these studies focuses on the amplitudes of EM tidal signals. This study investigates the phases of EM tidal signals and their changes. Twenty‐six years of monthly observation‐based datasets of tidal velocities, geomagnetic field, and oceanic conductivity are fed into an EM induction solver to generate varying EM tidal signals. The sensitivities of the resulting EM signals are analyzed by forbidding or allowing the input datasets to vary in time. We report on the phase's sensitivities with respect to changes in the EM properties, that is, secular variation of the geomagnetic field and changes in oceanic conductivity. Distinct temporal behavior and distinct geographic pattern for the two sensitivities can be reported. In general, apart from global phase shifts of 3–5 degrees, concentrated areas with phase shifts of up to 45 degrees occur all over the globe, over the oceans, for example, Arctic and Atlantic Ocean, as well as on coastal land regions, for example, Southwest Greenland and Japan. Very locally, phase shifts of 90 degree or higher occur. Key Points: Electromagnetic tidal signals show significant spatiotemporal phase changes. Annual and monthly phase anomalies are found to be of oceanic origin. Decadal transient phase anomalies are generated by secular variation and changing oceanic conductivity.